Localization of Aquaporin-1 in the small and large intestines of Geese (Anser anser) - Sari, Ebru Karadag (Slovenian veterinary research, 2024)
Aquaporins are selective water channels that serve transportation of wa-ter across cell membranes, which play a vital role in all cells. In this study, using the immunohistochemical method, the authors intended to investigate the localization of Aquaporin-1 in the small and large intestines of geese. In this study, small and large in-testine tissue samples taken from healthy adult geese (Anser anser) (n = 10) were used as materials. After fixation for 24 hours at 10% formaldehyde, the tissue samples were passed through graded series of ethanol and xylol and embedded in paraffin. Mallory's modified triple-staining method was used to examine the general structure of the in-testine. The Avidin-Biotin-Peroxidase Complex (ABC) method was applied to determine the immunoreactivity of Aquaporin-1. The apical parts of crypt epithelial cells showed strong Aquaporin-1 immunoreactivity in the duodenum and moderate Aquaporin1 im-munoreactivity in the jejunum and ileum. Strong Aquaporin-1 immunoreactivity was de-termined in vascular endothelial cells in the duodenum, jejunum, and ileum, and weak immunoreactivity was found in smooth muscle cells. However, a weak Aquaporin-1 im-munoreactivity was detected only in the smooth muscle cells of the cecum and rectum but not in vascular endothelial cells and crypt epithelial cells. The intestine tissue regu-lates salt transport and hydrostatic pressure differences, enabling the transportation of water. It was suggested that the duodenum and jejunum sections in particular are permeable to high levels of water for balancing the osmotic pressure of the intestinal content. Consequently, with this study, Aquaporin-1 immunoreactivity was detected in the crypt epithelial cells, smooth muscle cells, and vascular endothelium of the small intestines of geese.
Keywords: Aquaporin-1; geese; intestine